2017
DOI: 10.1002/14651858.cd011640.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for non-alcohol related fatty liver disease (NAFLD)

Abstract: Due to the very low quality evidence, we are very uncertain about the effectiveness of pharmacological treatments for people with NAFLD including those with steatohepatitis. Further well-designed randomised clinical trials with sufficiently large sample sizes are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 184 publications
0
49
0
3
Order By: Relevance
“…An understanding of the demographic and clinical factors associated with disease progression and mortality can lead to better stratification of high‐risk patients and support the efforts of public health policy makers to target interventions to those patients at greatest risk of more rapid disease progression. This is particularly relevant as novel medical therapies for NAFLD/NASH with the potential to halt or reverse disease progression undergo evaluation 18‐20 . Furthermore, the late identification of NAFLD/NASH in real‐world clinical practice and the high clinical burden found in this study for Medicare patients have broad public health implications.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An understanding of the demographic and clinical factors associated with disease progression and mortality can lead to better stratification of high‐risk patients and support the efforts of public health policy makers to target interventions to those patients at greatest risk of more rapid disease progression. This is particularly relevant as novel medical therapies for NAFLD/NASH with the potential to halt or reverse disease progression undergo evaluation 18‐20 . Furthermore, the late identification of NAFLD/NASH in real‐world clinical practice and the high clinical burden found in this study for Medicare patients have broad public health implications.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment guidelines currently do not recommend screening to identify NAFLD/NASH patients based on evidence that such screening is not cost‐effective due to limited efficacy of currently available treatment options 17 . However, with promising novel NAFLD/NASH interventions currently under development and review, and the substantial under‐diagnosis of NAFLD/NASH in the Medicare population, the impetus may be increasing for the need of an algorithm to identify individuals at high risk of NAFLD/NASH 18‐20 . Such an algorithm may decrease the clinical burden of the disease by helping to identify pre‐symptomatic patients and thereby allowing for earlier clinical intervention and management.…”
Section: Discussionmentioning
confidence: 99%
“…The major issue in this field is the scarcity of high-quality, randomized, blinded, adequately powered, controlled trials of sufficient duration and with clinically relevant endpoints. In line with this consideration, a recent Cochrane review 170 concluded that "we are very uncertain about the effectiveness of pharmacological treatments for people with NAFLD, including those with NASH". Some concerns also remain about the longterm safety of the available drugs, necessitating thoughtful balancing of the potential risks and benefits.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Lifestyle modification is the mainstay of treatment, with uncertainty regarding the effectiveness of drug therapy for patients with NAFLD 1. Exercise intervention studies demonstrate that exercise effectively reduces liver fat, even in the absence of significant weight loss.…”
Section: Contextmentioning
confidence: 99%